SPH simulation of periodic wave breaking in the surf zone - A detailed fluid dynamic validation. (15th March 2019) - Roselli, Riccardo Angelini Rota; Vernengo, Giuliano; Brizzolara, Stefano; Guercio, Roberto
Abstract: The estimation of wave breaking and run-up on sloped beaches is a relevant issue in different coastal engineering applications. The present study stresses on the capabilities of a Smoothed Particle Hydrodynamics (SPH) solver, with optimal numerical and physical parameters, to accurately simulate the complex flow field in the surf zone and run-up region. Numerical results are compared with high quality experimental measurements of the local flow field in terms of instantaneous and phase averaged values. The selected test case regards the propagation and breaking of regular non-linear waves on a smooth impermeable plane slope. The comparison is based on a complete set of 128 consecutive non-linear regular waves. The level of accuracy of the numerical results and the ability of the model to reproduce the periodic flow in the surf-zone is provided. Current limitations and uncertainty sources are identified and discussed to guide future developments. Highlights: An open-source SPH solver is used to reproduce wave transformations and breaking in the surf-zone. The SPH prediction is validated by comparison against experimental data available in literature. Istantaneous free surface shape and phase-averages on 128 consecutive waves have been analyzed. Steady state wave breaking kinematics over a large number of consecutive periodic waves is analyzed. Free surface phase-to-phase repeatability confirms reliable prediction of the wave profile up to breaking.